PADANAN PINTAR: TOWARDS A GAME-BASED APPROACH FOR REGULATING SENSORY AND EMOTIONAL OVERLOAD IN CHILDREN WITH ASD (Journal of Creative Industry and Sustainable Culture, 2024)
This research aimed to develop an interactive game application to help children with Autism Spectrum Disorder (ASD) manage sensory and emotional overload, which often leads to behavioural issues like tantrums. The game was designed by gaining a deeper understanding of ASD through interviews and observations. Key game requirements were identified to create an optimal experience for this specific audience. The result was the development of Padanan Pintar, a mobile application aimed at reducing sensory overload while promoting emotional regulation in children with ASD. Additionally, the game has the potential to improve cognitive skills by maintaining control over emotional and behavioural responses. User testing with autistic children showed positive engagement, emotional reactions, and behavioural outcomes. These results suggest that the game effectively provides a calming effect, minimizes sensory overload, and encourages relaxation.